Pre-Service English Teachers’ Anxiety in Speaking English: A Case from an Indonesian Islamic College - Ashari, Ali; Hamiddin, Hamiddin; Ainiyah, Inayatul; Diana Khalidah, Nur; Ubaidillah, M. Faruq; Mac Donald, Kara (Universitas Negeri Malang, 2023)
Extensive research on speaking English as a foreign language has been carried out in the last decades. However, little is known about the exploration of speaking anxiety experienced by pre-service English teachers situated at a private Islamic institute, particularly in the Indonesian setting. This case study aimed to investigate the factors that influence six pre-service English teachers’ anxiety in speaking English and how they overcome such hindrances. Data were analyzed using Braun and Clarke’s (2006) thematic analysis, including (1) familiarizing we with the talking data, (2) creating transcripts from the data, (3) reading the transcripts multiple times, (4) creating codes for salient data, (5) creating categories from the codes, and (6) creating themes from the categories. The analysis reveals factors that influence the participants’ speaking anxiety, including 1) feeling embarrassed, 2) fear of mistakes, 3) lack of confidence, 4) feeling nervous, and 4) rarely speaking. In addition, the participants enacted multiple ways of alleviating their anxiety when teaching, such as asking motivation from friends, starting the class with English, engaging, students in a game-based learning, preparing materials before the class, and asking students to focus on the class